A comparative study to evaluate the efficacy of EGF, FGF-2, and 0.3% (w/v) ofloxacin drops on eardrum regeneration. Issue 30 (July 2017) - Lou, Zhengcai; Lou, Zihan
Abstract: Background: Traumatic tympanic membrane perforations (TMPs) tend to spontaneous healing, however, large TMPs usually fail to healing. Clinical and experimental studies had demonstrated that growth factors accelerated the healing of large TMPs. The aim of this study was to compare the effects of growth factors and 0.3% (w/v) ofloxacin drops n the healing of human large TMPs. Methods: A total of 184 human large traumatic TMPs were randomly assigned to receive epidermal growth factor (EGF) treatment, fibroblast growth factor-2 (FGF-2) treatment, 0.3% (w/v) ofloxacin drops treatment, and conservative observation (only). Results: A total of 180 patients were analyzed in this study at the 6-month follow-up. The closure rates of the perforations in the EGF, FGF-2, 0.3% (w/v) ofloxacin drops, and conservative observation groups were 91.11%, 93.18%, 95.65%, and 82.22%, respectively, the closure rates did not significantly differ among the groups ( P = .165). Similarly, pairwise comparisons did not reveal any significant between-group differences ( P > .0083). However, the difference of the mean closure time was significant among the 4 groups ( P < .001), pairwise comparisons showed that closure time was significantly longer in the observational group than in the other 3 groups ( P < .001). Nevertheless, no significant difference in mean closure time was evident between any 2 treated groups ( P > .0083). The mean hearing gain after 6 months was 11.49 ± 5.88 dB for the EGF group, 10.89 ± 5.16 dB for the FGF-2 group, 10.54 ± 5.56 dB for the ofloxacin group, and 9.29 ± 5.36 dB for the observation group. Differences in hearing improvement rates among the 4 groups were not statistically significant ( P = .283). Conclusion: Epidermal growth factor, FGF-2, and 0.3% (w/v) ofloxacin drops accelerated the closure of large TMPs compared with conservative treatment. Surprisingly, neither the closure rate nor closure time differed significantly among the 3 treated groups. Further experimental studies to demonstrate whether 0.3% (w/v) ofloxacin per se accelerates the healing of TMPs will be interesting in the future.